황해 지역의 질소와 황 침적 추정 - 김진영; 김영성; 이승복; 문길주 (한국대기환경학회, 2003)
The amounts of nitrogen and sulfur deposited in the region of the Yellow Sea in both dry and wet forms wereestimated by using the measurement data published in the literature during the past 10 years. In the estimation ofdry deposition, concentrations at ground stations including those at a station on the Chinese side and concentrationsfrom shipboard and aircraft measurements were used as well as deposition velocities. Wet deposition ux wasfrom precipitation data in the literature. The dry deposition ux over the Yellow Sea was much greater than thosefor other world oceans; it was rather close to those estimated on the Korean Peninsula. Substantial inuence fromChina was conrmed from the fact that the total amount summing wet and dry depositions exceeded the emissionamount from Korea. Dry deposition was principally made in the gaseous form due to a larger deposition velocity.oxidized nitrogen was smaller than wet deposition. As a whole, wet depositions of nitrogen and sulfur were 2.3 and1.9 times larger than corresponding dry depositions, respectively.